Assessment of benzodiazepine dosing in status epilepticus patients in the emergency department - Aljadeed, Raniah Ibrahim; Alkaf, Amenah; Alhajlbrahim, Daad; Alewairdhi, Huda; Assiri, Ghadah Asaad; Aljadeed, Rana; Almalag, Haya; Kalagi, Nora (Frontiers in Neurology, 2025)
BackgroundStatus epilepticus (SE) is a medical emergency that requires immediate care and is associated with substantial mortality and morbidity. Current guidelines recommend benzodiazepines (BZDs), regardless of the type of SE, as an initial treatment. Despite established guidelines, BZD underdosing remains common in clinical practice. This study aimed to the objective of this study was to assess BZD doses in patients administered to the ED with SE and evaluate patient outcomes in relation to BZD dosing adequacy.MethodsWe conducted a single-center retrospective study of adult patients (≥18 years) who presented to the ED with SE and received BZDs from January 2021 to January 2024. Primary outcome was percent of SE patients admitted to our institution who received inadequate doses of BZDs. Secondary outcomes included ICU admission rates, need for endotracheal intubation, duration of mechanical ventilation, Glasgow Coma Scale (GCS) at discharge administration of second-line antiseizure medications, and in-hospital mortality. Demographic data, treatment details, and outcomes were collected and analyzed.ResultsAmong 196 adult patients included, only 17% (n = 34) received an adequate first dose of BZDs. Pre-hospital BZD administration occurred in 5% of cases. Lorazepam was most frequently administered (65%), followed by midazolam (20%) and diazepam (15%). Inadequate dosing rates were 77.2% for lorazepam, 90.0% for midazolam, and 96.6% for diazepam. Following first dose of BZE, the overall need for endotracheal intubation rate was 8.7% and in-hospital mortality at 3.1% across the entire cohort, with no significant differences between the 2 groups (p = 0.166; p = 0.279). The overall need for endotracheal intubation rate was 8.9%, with no statistically significant difference observed between the groups (p = 0.167). For patients requiring mechanical ventilation, the mean duration was 4 days (p = 0.988). Notably, inadequate total BZD dosing was significantly associated with increased in-hospital mortality (4.2% vs. 0%, p = 0.010).ConclusionBZD underdosing in SE management remains widespread, with only 17% of patients receiving guideline-adherent initial doses. Although our study did not demonstrate significant differences in clinical outcomes based on dosing adequacy, implementation of institution-specific protocols and focused educational initiatives on weight-based BZD administration may improve guideline adherence in SE management.